Trastornos depresivos en las personas adultas mayores de la Asociación de Ancianos Vilcabamba y estrategias de afrontamiento para potenciar su salud mental - Macas Granda, Silvana Elizabeth (2015)
The present research expected to determine the main depressive disorders in the older people of the Elders; Association Vilcabamba; to identify the most used strategies of confrontation to attenuate the depression; and, to elaborate an educational workshop as response to detected needs promoting in this way the well-being of the older people. The methodology was of descriptive and transverse type which universe and sample was constituted by 50 older people of the Elders; Association Vilcabamba, located in the Eternal Youth Av. of the Vilcabamba parish of the Loja canton. The Yesavage test was applied and served to know the depressive disorders; and the questionnaire of confrontation strategies; obtaining the following results: Self-criticism 78%, followed by the cognitive Restructuring with 70%, and the strategy corresponding to the emotional Expression with 64%. Being the slight depression with 46%and the depression moderated with 12%, the most frequent depressive disorders in the Elders; Association Vilcabamba; since the problematic of the Association before mentioned, it was demonstrated in base of the applied test that the depression is found infra-diagnosed, what carries the authorities and managers of health of these centers to consider the possibility of using instruments that value in an integral way the older population’s state of health at the moment, which will allow to establish a suitable treatment; efforts should be made with the whole health staff and the older people to the construction of a social positive image, on having stimulated the strategies of confrontation that allows to achieve the interest of these ones in stressful situations by means of activities that imply the overcoming of the same ones; it is necessary the implementation of an offer of leisure and occupational services directed this age bracket, the one that is in conformity and in correspondence with the interests of the older people, in such a way that contributes tore cover their capacity of possession, re-discovering their capacities and connecting with their desires, at the same time that the sense of freedom and self-esteem is stimulated. Key words: Depressive disorders, strategies of confrontation, older people.